Experimental investigations of aeration efficiency in high-head gated circular conduits - Tuna, M. Cihat; Ozkan, Fahri; Baylar, Ahmet (Iwa Publishing, 2014)
The primary purpose of water aeration is to increase the oxygen saturation of the water. This can be achieved by using hydraulic structures because of substantial air bubble entrainment at these structures. Closed conduit aeration is a particular instance of this. While there has been a great deal of research on air-demand ratio within closed conduit, very little research has specifically addressed aeration efficiency of closed conduit. In the present work an experimental study was conducted to investigate the aeration efficiency of high-head gated circular conduits. Results showed that high-head gated circular conduits were effective for oxygen transfer. The effects of Froude number and ratio of the water cross-sectional flow area to the conduit cross-sectional area on aeration efficiency were particularly significant, whereas the effect of conduit length was only moderate. Further, a design formula for the aeration efficiency was presented relating the aeration efficiency to ratio of water cross-sectional flow area to conduit cross-sectional area and Froude number. The obtained results will be useful in future modeling processes and aid the practicing engineer in predicting aeration efficiency for design purposes.
Keywords: aeration efficiency; air-water flow; conduit; high-head flow; oxygen transfer